The Berkeley sample of Type II supernovae: BVRI light curves and spectroscopy of 55 SNe II. Issue 2 (30th September 2019) - de Jaeger, T; Zheng, W; Stahl, B E; Filippenko, A V; Brink, T G; Bigley, A; Blanchard, K; Blanchard, P K; Bradley, J; Cargill, S K; Casper, C; Cenko, S B; et al.
ABSTRACT: In this work, BVRI light curves of 55 Type II supernovae (SNe II) from the Lick Observatory Supernova Search programme obtained with the Katzman Automatic Imaging Telescope and the 1 m Nickel telescope from 2006 to 2018 are presented. Additionally, more than 150 spectra gathered with the 3 m Shane telescope are published. We conduct an analyse of the peak absolute magnitudes, decline rates, and time durations of different phases of the light and colour curves. Typically, our light curves are sampled with a median cadence of 5.5 d for a total of 5093 photometric points. In average, V -band plateau declines with a rate of 1.29 mag (100 d) −1, which is consistent with previously published samples. For each band, the plateau slope correlates with the plateau length and the absolute peak magnitude: SNe II with steeper decline have shorter plateau duration and are brighter. A time-evolution analysis of spectral lines in term of velocities and pseudo-equivalent widths is also presented in this paper. Our spectroscopic sample ranges between 1 and 200 d post-explosion and has a median ejecta expansion velocity at 50 d post-explosion of 6500 km s −1 (H α line) and a standard dispersion of 2000 km s −1 . Nebular spectra are in good agreement with theoretical models using a progenitor star having a mass <16M⊙ . All the data are available to the community and will help to understand SN II diversity better, and therefore to improve their utility as cosmological distance indicators.